EFEKTIVITAS PELAKSANAAN MEDIASI DALAM PENYELESAIAN PERKARA PERCERAIAN DI PENGADILAN AGAMA BANYUWANGI TAHUN 2015-2017 - M. Mutamakin , Elfa Fiidinillah Putri (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2018)
This research was conducted to find out the effectiveness of the implementation of mediation in the resolution of litigated divorce court religion of Banyuwangi. This research is the research field. Based on the results of the analysis of the effectiveness of mediation in divorce court religion of Banyuwangi, pointed out that mediation has not been effective. Data obtained from the results of research on the implementation of the peace efforts by the mediators of the religious Courts in Banyuwangi based on regulations and rules of the Supreme Court of the Republic of Indonesia number 1 Year 2016 indicate the level of the success of mediation has not been fullest as only 58 cases successfully reconciled through the mediation process from 2,167 cases mediated or only reached 1.25% during year 2015-2017 time brackets.